Domains of Archean mantle lithosphere deciphered by seismic anisotropy- initial results from the LAPNET array in northern Fennoscandia - Plomerová, Jaroslava; Vecsey, L.; Babuška, V.; LAPNET Working Group; Heikkinen, Pekka; Komminaho, Kari (Solid Earth, 2017)
Peer reviewed